Physiology and production of naturally-colored cotton under irrigation strategies using salinized water - Soares, Lauriane Almeida dos Anjos; Fernandes, Pedro Dantas; Lima, Geovani Soares de; Brito, Marcos Eric Barbosa; Nascimento, Ronaldo do; Arriel, Nair Helena Castro (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effects of irrigation management strategies, using low (0.8 dS m-1) and high (9.0 dS m-1) salinity water, on the physiological processes, production variables, and fiber productivity of naturally-colored cotton (Gossypium hirsutum) genotypes during different phenological stages. Three naturally-colored cotton cultivars (BRS Rubi, BRS Topázio, and BRS Safira) were subjected to seven irrigation management strategies, in a 3x7 factorial arrangement, in a randomized complete block design with three replicates. Plants were cultivated in pots in a protected environment. Gas exchange, chlorophyll a fluorescence, fiber production, and productivity and yield variables were evaluated. Salt stress causes greater reductions in gas exchange in natural cotton plants during the production stage. Plume cotton production is not compromised by the use of highly salinized water during the initial developmental stages of naturally-colored cotton.